Basic concepts of Islamic education: The perspective of Al-Rahiq Al-Makhtum kitab - Hunainah, Hunainah; Ikhwansyah, Muhammad Fuad; Ramdhani, Muhammad Tri (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
The basics of Islamic education are used not only as the main pillar but also as a filter when problems arise. In Indonesia, various problems in the field are allegedly a manifestation of the face of national education. One of the best books that can be extracted from it, the basis of Islamic education sourced from the life of the Prophet Muhammad, is the Kitab of Al-Rahiq Al-Makhtum. This type of research is qualitative because it aims to explore the basis of Islamic education in related books, with the research method using library research. Primary data in this study are writings extracted from primary sources, namely the Kitab of Al-Rahiq Al-Makhtum by Al-Mubarakfuri. The secondary data in this study are writings extracted from supporting sources, books, and related journals. The data analysis technique used in this literature research uses the content analysis method. The results showed that the basis of Islamic education taught directly by the Prophet Muhammad Saw. and contained in the Kitab Al-Rahiq Al-Makhtum there are three pillars: The first is monotheism, the second is following the revelation, the third is good character, which includes patience, professionalism, tawadhu', and being able to be a role model. Based on this, every Muslim teacher and educator should realize and even absorb this meaning and try as much as possible to implement it in teaching so that all parties can overcome moral degradation together.